2015
DOI: 10.1038/srep16486
|View full text |Cite
|
Sign up to set email alerts
|

Olfaction and topography, but not magnetic cues, control navigation in a pelagic seabird: displacements with shearwaters in the Mediterranean Sea

Abstract: Pelagic seabirds wander the open oceans then return accurately to their habitual nest-sites. We investigated the effects of sensory manipulation on oceanic navigation in Scopoli’s shearwaters (Calonectris diomedea) breeding at Pianosa island (Italy), by displacing them 400 km from their colony and tracking them. A recent experiment on Atlantic shearwaters (Cory’s shearwater, Calonectris borealis) breeding in the Azores indicated a crucial role of olfaction over the open ocean, but left open the question of whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
74
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 67 publications
(80 citation statements)
references
References 34 publications
6
74
0
Order By: Relevance
“…While the temporal resolution of our tracking data was too coarse (4-to 12-min intervals between GPS locations) to identify fine-scale details of these flight paths, the highly consistent distribution of tracks across years suggests that persistent flight paths do occur. The literature suggests that social information exchange is most likely to be the driver of the consistency in the flight paths observed here; however, other factors such as avoidance of topographical features or olfactory cues may also influence these distributions (Pollonara et al 2015, Yonehara et al 2016. One other possible reason for increased flight through this area is that the west coast of the island faces the Atlantic Ocean.…”
Section: Discussionmentioning
confidence: 69%
“…While the temporal resolution of our tracking data was too coarse (4-to 12-min intervals between GPS locations) to identify fine-scale details of these flight paths, the highly consistent distribution of tracks across years suggests that persistent flight paths do occur. The literature suggests that social information exchange is most likely to be the driver of the consistency in the flight paths observed here; however, other factors such as avoidance of topographical features or olfactory cues may also influence these distributions (Pollonara et al 2015, Yonehara et al 2016. One other possible reason for increased flight through this area is that the west coast of the island faces the Atlantic Ocean.…”
Section: Discussionmentioning
confidence: 69%
“…Support for this hypothesis comes, in part, from displacement experiments on homing pigeons ( Colubma livia domestica ) and shearwaters (Procellariiformes) where olfactory deprivation led to reduced navigational ability27282930. A recent displacement study on lesser black-backed gulls ( Larus fuscus ) suggested that experimentally-induced anosmia led to impaired navigation performance in one of two release sites10.…”
mentioning
confidence: 99%
“…Once at the release site, pigeons may be able to determine the direction of displacement simply by recognising the prevalent local odours and recalling from which direction these arrived at the home loft. Although recent tracking studies on wild birds supported the critical role of olfactory information in avian navigation Pollonara et al, 2015;Wikelski et al, 2015), evidence supporting olfactory navigation in homing pigeons comes almost exclusively from traditional experiments in which vanishing bearings and homing performance were recorded. In fact, the only exception is a tracking study (Gagliardo et al, 2011b) reporting that pigeons made temporarily anosmic by anaesthetising their olfactory mucosa displayed impaired navigational abilities, unless they had been allowed to smell local environmental odours during transportation and at the release site prior to the release.…”
Section: Introductionmentioning
confidence: 99%